2017
DOI: 10.1007/s00248-017-1118-4
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive Soil Archaeal Communities in Different Variants of Tropical Equatorial Forest

Abstract: Little is known of how soil archaeal community composition and diversity differ between local variants of tropical rainforests. We hypothesized that (1) as with plants, animals, fungi, and bacteria, the soil archaeal community would differ between different variants of tropical forest; (2) that spatially rarer forest variants would have a less diverse archaeal community than common ones; (3) that a history of forest disturbance would decrease archaeal alpha- and beta-diversity; and (4) that archaeal distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 75 publications
3
3
0
Order By: Relevance
“…This might be due to differences in environmental adaptations, cellular structure, and cellular metabolisms between bacteria and archaea (31)(32)(33). Our findings are consistent with those of other studies that have reported the dominant role of stochastic processes in structuring the soil archaeal communities in forests (18,43) and farmland (47). However, other studies have also revealed only a minor role of stochastic processes in governing the archaeal community assemblies in the Namib Desert (45) and in agricultural fields across eastern China (46).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This might be due to differences in environmental adaptations, cellular structure, and cellular metabolisms between bacteria and archaea (31)(32)(33). Our findings are consistent with those of other studies that have reported the dominant role of stochastic processes in structuring the soil archaeal communities in forests (18,43) and farmland (47). However, other studies have also revealed only a minor role of stochastic processes in governing the archaeal community assemblies in the Namib Desert (45) and in agricultural fields across eastern China (46).…”
Section: Discussionsupporting
confidence: 90%
“…Generally, the deterministic and stochastic processes are recognized to simultaneously govern the community assemblies (7,8). Extensive studies have been conducted to determine the balance between stochastic and deterministic processes governing archaeal community assembly across various ecosystems, namely, freshwater lake (20), forest (18,42,43), coastal zone (44), desert (45), and agricultural (46) ecosystems. In this study, the results of both the NCM and null model analyses suggested that unlike the deterministic process-dominated bacterial community assembly (30), soil archaeal communities are dominated by stochastic processes in coastal wetlands (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Variation in pH (r ¼ 0.349, p , 0.01) and NO À 2 ÀN (r ¼ À0.251, p , 0.05) levels also had significant effects on the unweighted UniFrac distance of the benthic prokaryotic community, similar to previous studies (Tripathi et al 2015). This indicates that these two environmental factors may stimulate the benthic microbial community to generate turnover signals, followed by shifts in phylogenetic variation and geochemical function (Kerfahi et al 2018). In addition, under salinity stress, E. coli significantly inhibited the dominance of archaea and enhanced the dominance of bacteria (p , 0.001, Supplementary Fig.…”
Section: Benthic Microbial Community Succession Stability and Biogeoc...supporting
confidence: 84%